Application of Health Education to Improve Care Giver Knowledge - Almita Dwi Stevani; Indah Meilia Suryani; Warisah Handayani (Indonesian Journal of Global Health Research, 2022)
Elderly is the final period of the human life cycle, the aging process is marked by a decrease in body functions and behavior. One of the physical changes that occur is the emergence of degenerative and palliative diseases. Palliative is a chronic and terminal disease. Palliative cases were also found at the hopeful nursing home for mothers in Semarang. This study is a descriptive study about the description of the provision of health education about palliative elderly care at the hopeful nursing home for mothers in Semarang. The results showed that the average increase in knowledge after Health Education activities was 6.8. The results of the study describe that Health Education about palliative elderly care can increase the knowledge of the elderly.